Dinamika Perkembangan Kota Kecil dan Faktor-Faktor yang Mempengaruhinya (Studi Kasus pada Kecamatan Muntilan, Mungkid dan Salam) - Albertho Baga, Christofel Mario (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
Dynamic development of small towns can not be separated from the urbanization. The small towns are located along the road corridor that connects major cities experiencing rapid growth. It is also common in the District Mungkid, Muntilan and Salam which administratively belong to the small town. In the past 10 years, there have been additions village with city status, namely: in District Mungkid of 4 villages and in the District Salam much as 3 villages. In addition, there has been increased by 5% undeveloped land, in the villages located around the national road linking Semarang - Yogyakarta. It is also common in the increasing number of population density, where the concentration of the population are in the areas around the national road. Based on these descriptions, the question arises, how the dynamic development of the small town, and what are the factors that influence it? This study uses quantitative methods to assess the dynamics of a small town in terms of spatial, demographic, and social economic. The findings of this research study is the development of small town dynamics are affected by urbanization. Urbanization formed are influenced by social economic activities compared with the development of undeveloped land and population. From the analysis of the factors affecting the dynamics of a small town, there are several factors, such as: the location factor, accessibility, social, political, physical environment, and history. Based on the analysis, and interviews can be concluded that the development of small cities most affected by the location factor.